The potential of buffers (Acid Buf) or plant extracts (Xtract 7035) as natural alternatives for ionophores in lamb feedlot diets - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2019.